Characterization of genes used as selectable markers for the development of genetic sexing strains for SIT applications against tephritid pest species using CRISPR/Cas9 - Sollazzo, Germano; Justus Liebig University Giessen (My University, 2023)
Genetic sexing strains (GSSs) play a crucial role in the sterile insect technique (SIT), a powerful method employed in insect pest control and population management. SIT involves releasing sterile insects into target areas to suppress, eradicate, control, and prevent pest populations. However, in some cases, to ensure the effectiveness of this technique, it is essential to release only sterile males, as the females can still cause damage by laying eggs and/or biting. Male-only releases can be achieved by using GSSs, which are currently based on two selectable markers essential for sex separation and female elimination at the embryonic stage: the yet unknown temperature-sensitive lethal (tsl) gene and the recently identified white pupae (wp) gene, which have been used in the most successful GSSs developed thus far, the Ceratitis capitata (medfly) VIENNA 7 and VIENNA 8. In this work, I present three studies to narrow down the region where the Ceratitis capitata tsl gene is located and to identify tsl gene(s) and their causal mutation(s) responsible for the temperature-sensitive lethal phenotype. In the first study, I carried out temperature-sensitive lethal tests to determine the temperature sensitivity of twenty-seven Ceratitis capitata wild-type, genetic sexing, and tsl mutant strains, to assess differences among populations of different origins and to choose reference strains for the following investigations. In the second study, I used a combined approach of genomic, transcriptomic, bioinformatic, and cytogenetic data to characterize and analyze the putative tsl genomic region in Ceratitis capitata. This resulted in the identification of several potential candidate genes within the tsl region that could be associated with the temperature-sensitive lethal phenotype. These findings shed light on the underlying genetic mechanisms behind this phenotype and provide valuable insights for further investigations. In the third study, one of the potential tsl candidate genes previously identified, the deep orange (Ccdor) gene, was chosen to be targeted via CRISPR/Cas9 and to assess whether this triggers any temperature- sensitive lethal phenotype. I used CRISPR/Cas9-mediated NHEJ to knock out the Ccdor gene and CRISPR/Cas9-mediated HDR to successfully introduce a specific point mutation found in the tsl mutant strain. The latter resulted in the isolation of two additional mutations, leading to a temperature-sensitive lethal phenotype during embryonic, larval, and pupal stages. The results of this work represent steps forward for identifying potential markers that can be used to construct new GSSs in tephritids.
Keywords: Sterile Insect Technique; CRISPR/Cas9; Ceratitis capitata; Insect Biotechnology; ddc:500; ddc:570; ddc:630